Islam dan Islamisme: Analisis Perspektif Bassam Tibi dan Relevansinya di Indonesia - Dwi Utami Panggabean; Pefriani Pefriani; Tuti Alawiyah Matondang (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This study aims to examine the conceptual distinction between Islam and Islamism through the lens of Bassam Tibi’s intellectual framework and its relevance to Islamist groups in Indonesia. Bassam Tibi differentiates Islam as a religion founded upon spiritual values and universal ethics, whereas Islamism is conceived as a political ideology that seeks to instrumentalize Islamic doctrines for the pursuit of power. Employing a qualitative methodology grounded in literature-based analysis, this research evaluates Tibi’s major works and juxtaposes them with the contemporary religious dynamics of Indonesia. The findings demonstrate that Tibi’s perspective offers a reconciliatory framework for understanding divergent viewpoints within Muslim and Islamist communities in Indonesia. His theoretical contributions provide a robust foundation for analyzing the emergence and development of Islamist movements, particularly in relation to issues of religious, cultural, and ethnic diversity. In the Indonesian context, Islam—deeply rooted in local cultural traditions and national values—faces challenges from Islamist groups advocating transnational ideological agendas, including the establishment of an Islamic state and the formal implementation of shari‘a. These findings underscore the critical importance of distinguishing Islam as a religion from Islamism as a political ideology in order to preserve social harmony and sustain national cohesion. This study contributes to the advancement of contemporary Islamic studies and offers a comprehensive understanding of the phenomenon of religious politicization. Bassam Tibi’s perspective emerges as a relevant and analytically valuable framework for examining the multifaceted dynamics of interreligious, ethnic, and cultural relations in Indonesia.